Current and projected UK distribution of bryozoan host of the Proliferative Kidney Disease in salmonid fish - Rehman, Sarah (2022)
Proliferative kidney disease (PKD) has been identified as a main driver of decline in brown trout (Salmo trutta) populations across Europe.Tetracapsuloides bryosalmonae is the causative agent of PKD, leading to yearly aquaculture losses of >20%, costing the UK around £2.5 million per year. This study collates primary presence records of T. bryosalmonae’s primary host, the freshwater bryozoan Fredericella sultana. This data is utilised in species distribution modelling to identify areas predicted to be of high habitat suitability for F. sultana to infer species presence. Warming temperatures are known to exacerbate symptoms of PKD, making this an important system to study in the context of climate change. Therefore, data from the 6th phase of the Coupled Model Intercomparison Project (CMIP6) of the latest climate models are employed in this study to predict species range shifts, and inform on the potential of PKD spread across the UK in the coming decades. Maximum entropy modelling predicts optimal winter temperatures for F. sultana between 2-4°C, with a summer tolerance threshold of 16°C. The models also revealed that the future climates may increase habitats suitable for bryozoans in the north of the UK, with fewer areas of optimal winter climates in the south between the years 2041-2060. This information is essential in understanding the possible future threats of PKD, to tackle the issue of food insecurity and economic loss that will inevitably grow with global climate warming.